Implementasi Penatalaksanaan Gizi Pada Pasien Anak Dengan Diagnosa Epilepsi General Onset Motorik Tonik Etiologi Cerebral Palsy Tipe Diskinetik Disertai Pem Berat Tipe Marasmus Fase Rehabilitasi di Ruangan Bugenvile RSUP Prof. Dr. I.G.N.G Ngoerah - Endriani, Ni Made Dwi; Fanny, Lydia; Hartono, Rudy (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Epilepsy is defined as a brain disorder characterized by a tendency to cause continuous epileptic seizures with neurobiological, cognitive, psychological, and social consequences (1). The prevalence of epilepsy cases in Indonesia is 8.2 per 1,000 population with an incidence rate of 50 per 100,000 population. It is estimated that there are 1.8 million epilepsy patients who need treatment (2). The purpose of carrying out this case study is to implement diet management for patients with General Epilepsy Motor Onset Tonic Etiology Cerebral Palsy Type Diskinetic Type Accompanied by Weight Loss Type Marasmus Rehabilitation Phase in the Mother and Child VIP Room at RSUP Prof. I.G.N.G Ngoerah. This case study was carried out in the mother and child VIP room of Prof. I.G.N.G Ngoerah on April 8 - April 12, 2025. With a descriptive observational approach through Nutrition Care Process (NCP) including screening, assessment, diagnosis, intervention, monitoring and evaluation. Patients are at high risk of malnutrition with laboratory values related to nutrition not at normal limits and adequate patient intake. The patient was given a nutritional intervention in the form of a child's diet of 2560 kcal liquid food with gradual administration starting from 40% (1024 kcal) on the first day then increasing 55% (1400 kcal) on the second day, 75% (1920 kcal) on the third day and 80% (2048 kcal) on the fourth and fifth day by being given soft food and milk as a distraction. After monitoring and evaluation, there is an increase in intake, laboratory tests related to nutrition, and the patient's physical condition according to the planned target. With the improvement of the patient's condition, continuous monitoring is continued to support the nutritional and clinical recovery of the patient.